Schwannoma on Cervical Cervices (C2 & C3): A Case Report - Djoko Supriyandono, -
Abstract Background: Schwannoma is classified as a benign, encapsulated tumor, derived from the perineural cells which are classified as neural cell membranes. About 10% of Schwannomas has occurred in the head and neck and the incidence of Schwannoma arising from the Cervical C2 nerve roots is extremely rare. Aims of study: This case report aims to provide a rare case report on Schwannoma located in cervical cervices (C2& C3). Case presentation: A 37-year-old female patient with a lump in the left neck for 4 years ago, the first lump appeared as a larger (increasingly large 1×1 cm) marbles with no pain in the lump but over the past 4 months the patient felt his legs and arms are weak. Patients have a history of surgical removal of tumors in the back of the neckline by the end of 2016. At first, we estimated the lump that appeared on the left neck of the patient stands alone in the sense that it was not related to the history of the first lump surgery, but when further examination, the tumor was apparently related to the lump that appeared previously who had surgery. Conclusion: The extracranial Schwannoma in the head and neck areas is a rare neoplasm. The extracranial Schwannoma case is a case that is difficult to diagnose, in addition to good clinical examination, imaging examination, such as CT scan and MRI are an indispensable way of ensuring the diagnosis of an extracranial Schwannoma.